2020
DOI: 10.3390/ma13071616
|View full text |Cite
|
Sign up to set email alerts
|

The Chitosan Implementation into Cotton and Polyester/Cotton Blend Fabrics

Abstract: Chitosan is an environmentally friendly agent that is used to achieve the antimicrobial properties of textiles. Nowadays, the binding of chitosan to the textiles has been thoroughly researched due to the increasing demands on the stability of achieved properties during the textile care processes. Most crosslinking agents for chitosan are not safe for humans or environment, such as glutaric aldehyde (GA) and formaldehyde derivatives. Eco-friendly polycarboxyilic acids (PCAs) are usually used in after-treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 38 publications
(55 reference statements)
0
32
0
Order By: Relevance
“…A previous study point out that chitosan application improved tensile properties of cotton fabric. 49…”
Section: Analysis Results Of Chitosan-coated Fabricsmentioning
confidence: 99%
“…A previous study point out that chitosan application improved tensile properties of cotton fabric. 49…”
Section: Analysis Results Of Chitosan-coated Fabricsmentioning
confidence: 99%
“…Studies have shown that chitosan can reduce the harmful release of microplastics during the dyeing process [ 91 , 92 ]. Chitosan also has an antibacterial effect and is used in finishing to obtain antibacterial fibres [ 93 , 94 , 95 , 96 , 97 ]. Some studies have shown good resistance to washing and antibacterial activity of chitosan-treated fabrics against Staphylococcus aureus in up to five washing cycles [ 93 , 94 ].…”
Section: Mitigation Measures For Microplastic Contaminationmentioning
confidence: 99%
“…Chitosan also has an antibacterial effect and is used in finishing to obtain antibacterial fibres [ 93 , 94 , 95 , 96 , 97 ]. Some studies have shown good resistance to washing and antibacterial activity of chitosan-treated fabrics against Staphylococcus aureus in up to five washing cycles [ 93 , 94 ]. The treatment of polyester fabrics with chitosan leads to a significant antistatic effect in addition to its antibacterial properties.…”
Section: Mitigation Measures For Microplastic Contaminationmentioning
confidence: 99%
“…Literature data were used for the identification of bands in the infrared spectra for both cellulose and polyester fibres [20,28,29]. The polyester fibres in all tested fabric samples were identified as being made from polyethylene terephthalate.…”
Section: Micro-ftir Spectroscopy Analysismentioning
confidence: 99%